Assessment of stress distribution and displacement of complete dentures on flabby ridge with multiple occlusion schemes using finite element analysis - Ariyani; Ismet Danial Nasution; Maysfera, Nanda Iswa (Indonesian Journal of Prosthodontic, 2024)
ABSTRACT Background: Loss of teeth and supporting tissues, which are functional components of the stomatognathic system, significantly affects masticatory function. Flabby ridges are one of the soft tissue anomalies in the edentulous. The main choice of treatment for edentulous patients with flabby ridges issues is a complete denture (CD). Flabby ridges cause problems with the retention and stabilization of the CD which causes displacement of the denture base during function. Lingualized and linear occlusion schemes were used to overcome the stabilization of CD by reducing stress distribution in the flabby ridge area when obtaining masticatory load. Assessment of stress distribution and displacement of CD can be analyzed using Finite Element Analysis (FEA). Objectives: This paper describes the use of FEA to assess the stress distribution and displacement of CD on flabby ridges by simulating axial and oblique forces in lingualized and linear occlusion schemes. Conclusion: The use of FEA for assessing stress distribution and displacement of CD in flabby ridges with multiple occlusion schemes has advantages in terms of accuracy and flexibility. Keywords: finite element analysis, occlusion schemes, flabby ridges, stress distribution, displacement of complete denture